Pengaruh Green Marketing dan Environmental Awareness terhadap Keputusan Pembelian dengan Sikap Sebagai Variabel Mediasi (Studi pada Konsumen Mie Instan Lemonilo di Kota Kalianda): Penelitian - Putri Wijayanti; Herwanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of Green Marketing and Environmental Awareness on Purchasing Decisions, with Attitude as a mediating variable on Lemonilo Instant Noodle consumers in Kalianda City. This study uses a quantitative approach with a survey method, where data were collected through an online questionnaire using a purposive sampling technique on 120 respondents. Data analysis was carried out using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method through the SmartPLS 4 application. The results showed that Green Marketing had a positive and significant effect on Purchasing Decisions (coefficient = 0.381; T-statistic = 4.312; P-value = 0.000), as well as Environmental Awareness (coefficient = 0.351; T-statistic = 3.909; P-value = 0.000). Green Marketing and Environmental Awareness also had a positive effect on Attitude, with Environmental Awareness showing a stronger influence. Attitude is proven to have a positive influence on Purchasing Decisions (coefficient = 0.248; T-statistic = 2.592; P-value = 0.010). Attitude significantly mediates the influence of Environmental Awareness on Purchasing Decisions (coefficient = 0.119; T-statistic = 2.205; P-value = 0.028), but is not significant on the influence of Green Marketing on Purchasing Decisions (coefficient = 0.065; T-statistic = 1.616; P-value = 0.106).